How do climate-related conditions affect Norwegian enterprises? Results of three surveys in Norges Bank's regional network - Henriette Brekke; Solveig K. Erlandsen; Sara Skjeggestad Meyer (Norges Bank, 2023)
Climate change and the transition to a low-carbon economy affect the Norwegian and global economy in many ways. To gain greater insight into how these changes affect the Norwegian economy, Norges Bank has asked a selection of Norwegian enterprises on three occasions in recent years how climate-related conditions affect their operations. This report presents the results of the three surveys. In summary, the results show that climate-related conditions are important for most companies. In particular, factors related to the transition to a low-carbon economy, such as changing customer preferences and climate policy, are important for many of the companies. Climate change in the form of changing weather conditions is also important for many, but a smaller proportion state that this is very important for the company. Many companies see business opportunities in climate changes, but climate-related conditions also lead to higher costs and higher prices.
hdl:11250/3061858
Keywords: 330; Climate change; climate transition; Regional network